Selective Induction of Cancer Cell Death by Targeted Granzyme B - Robert A. Jabulowsky; Pranav Oberoi; Winfried S. Wels (Antibodies, 2013)
The potential utility of immunotoxins for cancer therapy has convincingly been demonstrated in clinical studies. Nevertheless, the high immunogenicity of their bacterial toxin domain represents a critical limitation, and has prompted the evaluation of cell-death inducing proteins of human origin as a basis for less immunogenic immunotoxin-like molecules. In this review, we focus on the current status and future prospects of targeted fusion proteins for cancer therapy that employ granzyme B (GrB) from cytotoxic lymphocytes as a cytotoxic moiety. Naturally, this serine protease plays a critical role in the immune defense by inducing apoptotic target cell death upon cleavage of intracellular substrates. Advances in understanding of the structure and function of GrB enabled the generation of chimeric fusion proteins that carry a heterologous cell binding domain for recognition of tumor-associated cell surface antigens. These hybrid molecules display high selectivity for cancer cells, with cell killing activities similar to that of corresponding recombinant toxins. Recent findings have helped to understand and circumvent intrinsic cell binding of GrB and susceptibility of the enzyme to inhibition by serpins. This now allows the rational design of optimized GrB derivatives that avoid sequestration by binding to non-target tissues, limit off-target effects, and overcome resistance mechanisms in tumor cells.